The Role of Job Satisfaction in Moderating of Human Resource Performance on Snack Company in Sidoarjo, Indonesia - Lailatul Hidayati; Rifdah Abadiyah (Indonesian Journal of Law and Economics Review, 2020)
This study aims to determine the effect of human resource information systems and competencies on employee performance and to determine the effect of human resource information systems and competencies on employee performance with job satisfaction as a moderating variable at PT. Manohara Asri Sidoarjo. Research Line includes the type of Quantitative Research, analysis tools used in the form of questionnaires. The population in this study was 334 employees of PT. Manohara Asri Krian. The sample in this study was 182 respondents. Data analysis was performed by path analysis using AMOS software. Research results show that the human resource information system has no significant effect on employee performance; competence has a significant effect on employee performance. In addition, the results show that the human resource information system and competence significantly influence employee performance with job satisfaction as a moderating variable.